IBM's global talent management strategy : the vision of the globally integrated enterprise. Part B - Boudreau, John W., (SAGE knowledge. Cases., 2016)
In early 2003, Randy MacDonald, the senior vice president of human resources for IBM Corporation, was reviewing his recent meeting with Sam Palmisano, the CEO of IBM. Randy had been the chief HR executive at IBM since 2000, joining when Lou Gerstner was in the middle of his tenure as IBM's CEO. Sam and Randy discussed IBM's strategic view of the evolution of global markets, IBM's strategic position as a leader in global transformation and the evolving needs of IBM's clients. Sam coined the phrase "Globally Integrated Enterprise" (GIE) to describe what he had in mind. He foresaw that IBM's clients would increasingly be moving toward a GIE and that IBM needed to get ahead of that trend.